The Surgery of Childhood Tumors - Carachi, Robert; Grosfeld, Jay L. (Springer Berlin Heidelberg : Imprint: Springer, 2016)
Beginning with the scientific basis of tumors, this book provides up-to-date information on epidemiology, cytogenetics, and molecular biology, before examining current treatments for the full range of pediatric tumors. Integration of surgery, neoadjuvant and adjuvant chemotherapy, and radiation therapy is a dominant theme. In addition, chapters on supportive care, palliative care, and the role of parents' associations reflect the book's holistic approach to treating children with cancer. The  Surgery of Childhood Tumors is written by world-renowned international authorities on pediatric cancer from major children's cancer groups in the UK, Europe, and the US. Contributors discuss geographical variations in treatment for each type of tumor. Excellent full-color pictures and line drawings illustrate all aspects of managing childhood tumors, including details of operative techniques which are neglected in many other texts. This comprehensive book provides a contemporary approach for pediatric, general, and urological surgeons dealing with childhood tumors. Since the second edition, the book has been significantly expanded and updated in order to encompass the very latest developments and strategies in pediatric surgical oncology.